2008
DOI: 10.1097/01.nne.0000334775.98018.e8
|View full text |Cite
|
Sign up to set email alerts
|

Podcasting

Abstract: Podcasting, a recently introduced technology, is being used increasingly in higher education. The authors provide an overview of the potential uses and techniques for implementing podcasting in nursing education. Their experiences with implementing podcasting in their nursing courses and the results of a survey on student feedback related to podcasting are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In the literature, various observational studies have demonstrated that the use of video streaming contributes to learning as a powerful instrument for education and for the acquisition of clinical competencies, reducing the gap between theory and practice [1012]. It has also been highlighted that knowledge is not only acquired through video observation, but as part of the students’ learning process.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, various observational studies have demonstrated that the use of video streaming contributes to learning as a powerful instrument for education and for the acquisition of clinical competencies, reducing the gap between theory and practice [1012]. It has also been highlighted that knowledge is not only acquired through video observation, but as part of the students’ learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of the use of podcasts in both undergraduate medical [27-29] and nurse education [30,31] in the U.K. and elsewhere are slowly beginning to emerge. Evaluative studies of the use of podcasts in medical education have indicated that podcasts helped students to learn their course materials and reduce their anxiety and stress relating to the subject [28] without impacting on classroom attendance [29].…”
Section: Introductionmentioning
confidence: 99%
“…Vogt et al, also discuss Siemans' connectivism theory along with Mayers' Multimedia Learning Theory -that students will learn through several avenues including visual and auditory -to frame their study of undergraduate nursing students' learning and satisfaction with podcasting (Vogt, Schaffner, Ribar, & Chavez, 2010). Others have reported survey results that focused on student satisfaction with the technology and the method of content delivery, though without a theoretical framework (Bollmeier, Wenger, & Forinash, 2010;Forbes & Hickey, 2008;Lymn & Bowskill, 2010;McKinney & Page, 2009;Nast et al, 2009;Patasi, Boozary, Hincke, & Jalali, 2009;Pilarski, Alan Johnstone, Pettepher, & Osheroff, 2008;Reynolds, Mason, & Eaton, 2008;Schlairet, 2010;Shantikumar, 2009;Walmsley et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One faculty concern is decreased student attendance in class. Some investigators did not find this to be a significant issue (Copley, 2007;Forbes & Hickey, 2008;Lymn & Bowskill, 2010;Meade, Bowskill, & Lymn, 2009;Nast et al, 2009;Pilarski et al, 2008), however, Kardong-Edgren (Kardong-Edgren & Emerson, 2010) found that faculty reported increasing student absenteeism after increased availability of podcasts. .…”
Section: Literature Reviewmentioning
confidence: 99%